Application of a digital marketing system in the development of Batik Sari Kenongo MSMEs in Sari Rogo Village - Lely Ika Mariyati; Ramon Ananda Paryontri; Bilqisth Nuruh Azizah (Community Empowerment, 2022)
Covid-19 has an impact on the activities of Micro, Small and Medium Enterprises (MSMEs) in Sari Rogo Village, Sidoarjo District, Sidorajo Regency. MSMEs have existed in this village for a long time, particularly the well-known Batik Sari Kenongo product. The development of SMEs Batik Sari Kenongo had ceased following the Covid-19 pandemic. The traditional marketing system was responsible for the suspension of UMKM Batik Sari Kenongo's development and the rapid decline in sales. To increase sales, developing Batik Sari Kenongo products through digital media requires training and assistance. The method used in this program is training and assistance in making digital media to promote the products. As a result of this program, partners capable of putting digital media marketing strategies into practice, enabling a larger and better-informed public to access information about Sari Kenongo batik.